Dynamic Response Analysis and Vibration Reduction of Steel Truss Corridor Pedestrian Bridge Under Pedestrian Load - Chen, Zhou; Chen, Zehong; Li, Guangjun; Zhang, Weixiong; Zhang, Xiaoqing; Huang, Shiping; Chen, Zepeng (Frontiers in Materials, 2022)
With the advancement in civil engineering, the applications of lightweight and high-strength materials, and large-span, low-damping structural systems, are increasing. One important structural system for such applications is the corridor pedestrian bridge structure. The vibration frequency of the corridor pedestrian bridge structure is often in the same range as the step frequency of pedestrians, and it is easy to cause the appearance of the corridor structure. Vibration comfort issues even affect the safe use of the corridor. Vibration comfort issues even affect the safe use of the corridor. Regarding the vertical vibration caused by pedestrians on the steel structure corridor footbridge, using a tuned mass damper (TMD) system can reduce the vibration effect. After the TMD vibration reduction test of the steel structure corridor footbridge, it can be found that the vibration reduction rate of the footbridge has reached 62.56%. The results show that vibration reduction by TMD system is a safe and effective method for pedestrian bridge vibration reduction, improving the structural performance and pedestrian comfort of the structural corridor pedestrian bridge.